INCORPORATING PUBLIC INPUT WITH GEOGRAPHIC INFORMATION SYSTEM (GIS) FOR BICYCLE STRATEGIC PLANNING: A Case Study of Grand Prairie, Texas - Jiangli Li; June Chae-Un (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2021)
Desire for active transportation is on the rise. However, the need for data and ways to incorporate public input in bicycle strategic planning are challenges faced by local governments with inadequate resources and time. The study aims to investigate mechanisms of input data by public which can included in the strategic planning of bicycles. Here, case study adopted a mix-methods approach to gather public input data in order to understand residents’ cycling patterns, needs, perceived barriers to cycling and preference for cycling facilities. The mix-methods approach included an intercept survey and several small group meetings. The non-probability sample design was used in this particular case because of the quick turn-around requirement and exploratory nature of the study with no financial resource. This paper presents a case study of bicycle strategic planning in the City of Grand Prairie, Texas. It illustrates how local governments can engage the public in bicycle planning through a public input process and use of GIS. The approach is useful for local governments elsewhere to meet their immediate needs for data and to promote active transportation with limited resources and time.